Cardiovascular risk factors and clinical presentation in acute coronary syndromes. Issue 9 (15th August 2005) - Rosengren, A; Wallentin, L; Simoons, M; Gitt, A K; Behar, S; Battler, A; Hasdai, D
Abstract : Objective: To investigate the hypothesis that risk factors may be differently related to severity of acute coronary syndromes (ACS), with ST elevation used as a marker of severe ACS. Design: Cross sectional study of patients with ACS. Setting: 103 hospitals in 25 countries in Europe and the Mediterranean basin. Patients: 10 253 patients with a discharge diagnosis of ACS in the Euro heart survey of ACS. Main outcome measures: Presenting with ST elevation ACS. Results: Patients with ACS who were smokers had an increased risk to present with ST elevation (age adjusted odds ratio (OR) 1.84, 95% confidence interval (CI) 1.67 to 2.02). Hypertension (OR 0.65, 95% CI 0.60 to 0.70) and high body mass index (BMI) (p for trend 0.0005) were associated with less ST elevation ACS. Diabetes mellitus was also associated with less ST elevation, but only among men. Prior disease (infarction, chronic angina, revascularisation) and treatment with aspirin, β blockers, or statins before admission were also associated with less ST elevation. After adjustment for age, sex, prior disease, and prior medication, smoking was still significantly associated with increased risk of ST elevation (OR 1.53, 95% CI 1.38 to 1.69), whereas hypertension was associated with reduced risk (OR 0.75, 95% CI 0.69 to 0.82). Obesity (BMI > 30 kg/m 2 versus < 25 kg/m 2 ) was independently associated with less risk of presenting with ST elevation among women, but not among men. Conclusion: Among patients with ACS, presenting with ST elevation is strongly associated with smoking, whereas hypertension and high BMI (in women) are associated with less ST elevation, independently of prior disease and medication.